Gothic Overtones: The Female Monster in Margaret Atwood’s “Lusus Naturae” - López Ramírez, Manuela (Complutense Journal of English Studies, 2021)
In “Lusus Naturae,” Margaret Atwood shows her predilection for the machinations of Gothic fiction. She resorts to gothic conventions to express female experience and explore the psychological but also the physical victimisation of the woman in a patriarchal system. Atwood employs the female monster metaphor to depict the passage from adolescence to womanhood through a girl who undergoes a metamorphosis into a “vampire” as a result of a disease, porphyria. The vampire as a liminal gothic figure, disrupts the boundaries between reality and fantasy/supernatural, human and inhuman/animal, life and death, good and evil, femme fatale and virgin maiden. By means of the metaphor of the vampire woman, Atwood unveils and contests the construction of a patriarchal gender ideology, which has appalling familial and social implications.